Yam Starch and Chitosan-Based Bioplastics to Improve Shelf Life of Pempek - Ulyarti Ulyarti; Ninada Ninada; Silvi Leila Rahmi; Agus Salim; Nazarudin Nazarudin (Postgraduate, University of Mataram, 2023)
This study aimed to determine the effect of yam starch and chitosan based-bioplastics packaging on the microbiological and sensory qualities of pempek during storage. This research was carried out by packing pempek using 2 different packaging: bioplastics and polyethylene plastic. Pempek in each group was stored for 0, 8, 16, 24, 48 hours at room temperature. The total of Staphylococcus aureus bacterial was determined using colony forming unit. Sensory quality was obtained by determination of color, texture and aroma of pempek using 5 skilled panelists. The result showed that the use of bioplastics packaging from yam starch and chitosan decreased the growth of Staphylococcus aureus bacteria in pempek compared to the use of polyethylene plastic packaging. The decrease in pH was in line with the growth of S.aureus that is higher in pempek packaged with polyethylene plastics. The use of bioplastics also maintained sensory qualities of pempek during storage better than polyethylene plastics